MASCULINITY AND MARGINALITY: PALESTINIAN MEN'S STRUGGLES WITH INFERTILITY IN ISRAEL AND LEBANON. - Birenbaum-Carmeli, Daphna; Inhorn, Marcia C. (Journal of Middle East Women's Studies (Indiana University Press))
Male infertility, which contributes to roughly 60-70% of infertility cases in the Middle East, is especially agonizing in this region, where fatherhood is crucial to achieving masculine adulthood and community standing. In this paper, we compare the infertility experience of two groups of Palestinian men, one living in Israel and the other in Lebanon. The study is based on ethnographic interviews conducted with 24 men between 2003 and 2007. The findings cluster at three levels of daily experience. At the subjective level, men express a sense of "asynchronization," namely, feeling as if they are lagging behind or deviating from the normal masculine l~[e trajectory. At the community level, men vary greatly in their disclosure practices, but all are preoccupied with monitoring the flow of infertility-related information. We attribute the centrality of this gate-keeping activity to the stigma of infertility and related treatments. At the societal level, the state's role acquires heightened significance, owing to the marginalized minority status of Palestinian men in both countries. Our comparison reveals two contrasting situations: In Lebanon, the high cost of treatment places it beyond the reach of many Palestinians, thus epitomizing their civil marginality and poverty. In Israel, where fertility treatment is state-funded, eligibility on the grounds of one's Israeli citizenship comprises a relatively positive experience for Palestinian men, who are otherwise routinely discriminated against in crucial life domains. More generally, the study illustrates how advanced fertility treatments, in their global spread, serve to entrench ideas of reproductive normalcy, individuality, and citizenship.